Social and material determinants of health in participants in an active labor market program in Barcelona - Patricia González-Marín; Vanessa Puig-Barrachina; Imma Cortès-Franch; Xavier Bartoll; Lucía Artazcoz; Davide Malmusi; Eva Clotet; Ferran Daban; Elia Díez; Àfrica Cardona; Carme Borrell (BMC, 2018)
Abstract Background Unemployment affects the physical and mental health of affected individuals, which can be explained by its direct effect on worsening finances due to the lack of income as well as by its negative psychosocial effects. "Employment in the Neighborhoods" return to work program was implemented in Barcelona specifically in the neighborhoods characterized with a greater economic deprivation and by high unemployment to improve personal and occupational abilities and skills of the participants to reintegrate them into the workforce. The aim of this study is to determine the association between the lack of economic resources and psychosocial factors with respect to mental health and self-rated health in unemployed persons participating in the program "Employment in the Neighborhoods". Methods Cross-sectional study. Data collected from a self-administered questionnaire. Generalized linear models were constructed, adjusted by age and social class, to estimate prevalence ratios and analyze any possible association between economic resources, psychosocial factors and poor self-rated health and mental health. Results Nine hundred forty-eight persons of 2763 participants in the "Employment in the Neighborhoods" program completed the questionnaire. 46.9% were women. 72.5% of women and 61.9% of men were at risk of poor mental health and 25.5% of women and 21.1% of men reported poor self-rated health. Low self-esteem [women: PR 1.88 95%CI (1.24-2.84); men: PR 2.51 95%CI (1.57-4.02)] and medium social support [2.01 (1.30-3.09)], in men, and low social support [1.74 (1.13-2.68)] in women are associated with worsening of self-rated health. In men, low self-esteem [1.40 (1.19-1.64)] and delay in paying bills [1.38 (1.17-1.64)] were associated with the risk of poor mental health; in women were associated low self-esteem [1.27 (1.11-1.44)] and received a non-contributory allowance [1.37 (1.09-1.74)]. Conclusions Economic resources, self-esteem and social support are necessary for good general and mental health among unemployed persons. The high prevalence of poor mental health among persons participating in the active labor market program "Employment in the Neighborhoods" could be due to a substantial deficit in these factors.